2019
DOI: 10.1073/pnas.1819154116
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella oxytoca enterotoxins tilimycin and tilivalline have distinct host DNA-damaging and microtubule-stabilizing activities

Abstract: Establishing causal links between bacterial metabolites and human intestinal disease is a significant challenge. This study reveals the molecular basis of antibiotic-associated hemorrhagic colitis (AAHC) caused by intestinal resident Klebsiella oxytoca. Colitogenic strains produce the nonribosomal peptides tilivalline and tilimycin. Here, we verify that these enterotoxins are present in the human intestine during active colitis and determine their concentrations in a murine disease model. Although both toxins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 58 publications
5
88
1
1
Order By: Relevance
“…The three cases where antibiotics were provided distant to the onset of disease suggest that other mechanisms also may be involved. Tilimycin, a cytotoxin produced by K. oxytoca, can mitigate the growth of commensal bacteria [40]. Thus, luminal conditions that enhance tilimycin synthesis could facilitate toxin-mediated reductions in microbial competition allowing K. oxytoca to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…The three cases where antibiotics were provided distant to the onset of disease suggest that other mechanisms also may be involved. Tilimycin, a cytotoxin produced by K. oxytoca, can mitigate the growth of commensal bacteria [40]. Thus, luminal conditions that enhance tilimycin synthesis could facilitate toxin-mediated reductions in microbial competition allowing K. oxytoca to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the antibiotic-resistance and virulence genes encoded by K. oxytoca and related species. In the course of ongoing Klebsiella-phage work, with three GES-5-positive clinical strains (8) of K. michiganensis, we sought to determine whether widely recognized virulence factors such as enterobactin, yersiniabactin and salmochelin are encoded in the strains' genomes, and the kleboxymycin biosynthetic gene cluster (BGC), as this was until recently a little-studied BGC implicated in non-Clostridioides difficile antibiotic-associated haemorrhagic colitis (AAHC) (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Another strain Klebsiella ( K. oxytoca ) secretes a small molecule called tilivalline (Tse et al, ), and this molecule was recently shown to arrest A549 cells at the G2/M stage (Unterhauser et al, ). Microtubule polymerization was enhanced by tilivalline in vitro , and more multipolar spindles were observed in mitotic cells exposed to tilivalline (Unterhauser et al, ). In contrast, K. pneumoniae disassembled microtubule networks of A549 cells (Chua et al, ), and in this study, we did not observe any multipolar spindles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, K. pneumoniae disassembled microtubule networks of A549 cells (Chua et al, ), and in this study, we did not observe any multipolar spindles. Additionally, the astral microtubules were not elongated in tilivalline‐treated mitotic cells (Unterhauser et al, ), suggesting that different mechanisms are employed by K. oxytoca and K. pneumoniae to cause cell cycle arrest. Regardless, cell cycle arrest has become a newly identified phenotype of Klebsiella infections, and through our study, we have shown that K. pneumoniae has devised its own mechanism to interfere with mitosis through the katanin family of proteins.…”
Section: Discussionmentioning
confidence: 99%